Communicative Arabic and Structure of Its Philosophical Teaching - Muhammad Rusydi (Langkawi: Journal of The Association for Arabic and English, 2018)
This article orients to expose the philosophical frame of communicative Arabic teaching. Communicative Arabic teaching has a strong philosophical framework because this modern teaching approach directs the Arabic language to its original position as a tool to communicate. In this context, the ontology dealing with the essence of Arabic teaching as a pedagogical reality, the epistemology dealing with its procedural framework and the ontology dealing with its value framework see that communicative Arabic teaching should be developed with a suitable educational philosophy reinforcing the Arabic to its functional-communicative framework. This article, finally, presents an alternative analysis to perceive communicative Arabic teaching.